Digital Single Market Bausteine eines Digitalen Binnenmarkts - Weller, Matthias; Wendland, Matthias (Mohr Siebeck, 2019)
The ongoing transformation of European law set in motion by digitalisation prompted the European Commission to come up with a strategy for creating a digital single market. With its interdisciplinary tour of the legal landscape, this conference volume provides an overview of the effects on private and civil procedure law.
PublicationDate: 20190826
Keywords: Zivilprozessrecht -- Europäisches Privatrecht -- europäische Verwaltung -- Versicherung für fremde Rechnung -- Digitalisierung -- welfare caseloads -- social assistance -- E-Justice -- Digitaler Binnenmarkt -- Bürgerliches Recht -- Zivilverfahrensrecht, Insolvenzrecht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung